Análise do viés de recordação de informações sobre lesões no futebol em adolescentes - Barbosa, Danielli Aguilar [UNESP] (2013)
Introduction: The Morbidity Survey is considered an effective tool for population analysis, in addition to low cost, it is a simple tool that can cover a variety of information for epidemiological studies. However, when adopts a time interval between the occurrence of the injury and its registration losses of information may occur, ie recall bias. The problem situation to be considered is whether adolescents soccer players can appropriately remember their characteristics and history of injuries after a period of four months. Considering that in sports initiation often there is a shortage of medical records and/or medical staff, and that the use of this method may be an alternative to facilitate the logistics of sampling and promote study’s feasibility. Objective: to analyze the recall bias of the characteristics of the injury (anatomic location, mechanism of injury, nature of injury, time of injury, severity of injury, return to normal activities and recurrences), of the anthropometric variables (body mass and height) and of the training (training time, hours weekly, faults and positioning) by means of the Morbidity Survey in adolescents who play soccer, during a period four months....